The Effect Of Home Country Economic Push Factors On Intention To Migrate: The Mediating Role Of Psychological Distress Among Professionals: A Conceptual Framework - Sabti, Yousif Mousa; Ramalu, Subramaniam Sri (International Journal of Rehabilitation and Special Education (IJRSE), 2021)
Purpose: The purpose of the study is to examine the  influence of home country economics push factors on the  intention to migrate among professionals, the mediating  effect of psychological distress. Methodology: This paper explores the effect of home  country economics push factors on intention to migrate  through previous literature. Results: This study considers appropriate propositions to  enhance the professional‘s intention to migrate. The study  develops related propositions, the home country economics push factors enhance the intention of migration.  Implications: Understanding professional's intentions to  migrate are crucial for the hospital management for the real  motives behind professional's intentions to migrate, which  will suggest them to make appropriate decisions. The suggestion eventually used for developing a conceptual  framework for future empirical research.
Keywords: Economics difficulties; Economics instability; Psychological distress; Intention to migrate